Reducing Staphylococcus aureus bloodstream infections associated with peripheral intravenous cannulae: successful implementation of a care bundle at a large Australian health service. Issue 1 (September 2016) - Rhodes, D.; Cheng, A.C.; McLellan, S.; Guerra, P.; Karanfilovska, D.; Aitchison, S.; Watson, K.; Bass, P.; Worth, L.J.
Summary: Background: Healthcare-associated Staphylococcus aureus bacteraemia (HA-SAB) results in morbidity, mortality, and increased healthcare costs, and these infections are frequently regarded as preventable. Aim: To implement a multi-modal prevention programme for improved processes regarding peripheral intravenous cannula (PIVC) insertion and maintenance, in order to reduce PIVC-associated HA-SAB events in a large Australian health service. Methods: Baseline clinical practice was evaluated for a 12-month pre-intervention period. Measures to reduce HA-SAB risk were introduced between January and September 2013: staff education, improved documentation (including phlebitis scoring), and availability of standardized equipment. Post-intervention auditing was performed during the 27 months following intervention. Baseline and post-intervention HA-SAB and PIVC-associated infection rates were compared. Interrupted time-series and Bayesian change-point analyses were applied to determine the impact of interventions and timing of change. Findings: Significantly improved documentation regarding PIVC insertion and management was observed in the post-intervention period, with fewer PIVCs left in situ for ≥4 days (2.6 vs 6.9%, P < 0.05). During the baseline period a total of 68 HA-SAB events occurred [1.01/10, 000 occupied bed-days (OBDs)] and 24 were PIVC-associated (35% of total, rate 0.39 per 10, 000 OBDs). In the post-intervention period, a total of 83 HA-SAB events occurred (0.99 per 10, 000 OBDs) and 12 were PIVC-associated (14.4% of total, rate 0.14 per 10, 000 OBDs). PIVC-associated SAB rates were 63% lower in the post-intervention period compared to baseline ( P = 0.018) with a change point observed following full bundle implementation in October 2013. Conclusion: A successful multi-modal hospital-wide campaign was introduced to reduce PIVC-associated SAB rates. Evaluation of cost-effectiveness and sustainability is required.